Clinical Management and Therapeutic Advances in Pediatric Patients with Neurofibromatosis Type 1 Associated Plexiform Neurofibromas - Karina Quintero; Lorelay Cárcamo; Andrés Bernales; Oleg Saldaña; Indira Herrera; Teresa Chavez; José Sotillo (Gene Clin Genom, 2026)
Introduction: Neurofibromatosis type 1 (NF1) is an autosomal dominant disorder frequently complicated by plexiform neurofibromas (PN), which cause severe functional impairment and present a complex therapeutic challenge. Methods: This descriptive case series evaluates four pediatric patients diagnosed with NF1 and progressive, symptomatic PN managed at a tertiary care children's hospital in Panama. Clinical records, histopathology, molecular treatment data, and serial Magnetic Resonance Imaging (MRI) or Computed Tomography scans were retrospectively analyzed to assess progression and treatment responses. Results: The cohort presented diverse manifestations, including orbital/craniofacial and spinal tumor involvement. Traditional surgical resections yielded limited efficacy due to the infiltrative nature of the lesions. However, targeted molecular therapy with the MEK inhibitor selumetinib initiated after traditional treatment failure led to substantial outcomes: Case 1 achieved a 27.7% volumetric tumor reduction within six months, and Case 3 demonstrated complete resolution of a paravertebral lesion concurrently with severe pain reduction (from 7 to 3 on the pain scale) and significant improvements in motor gait and quality of life. Conclusions: While surgical boundaries remain highly restricted in deep-tissue infiltrative PN, the introduction of targeted MEK inhibitors marks a pivotal therapeutic paradigm shift. Improving timely access to these therapies, alongside adequate monitoring, may help prevent further functional deterioration in selected pediatric patients, although larger, prospective studies are needed to confirm the magnitude and durability of this benefit.